2019
DOI: 10.1080/21691401.2019.1652631
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress promotes ventilator-induced lung injury through activating NLRP3 inflammasome and TRPM2 channel

Abstract: Ventilator has been widely used for life support, but ventilator-induced lung injury (VILI) is still a major problem. Oxidative stress has been considered as a key contributor for VILI, but the specific mechanism remains unclear. The expression of NLRP3 inflammasome in cells and inflammatory factors in the supernatant were measured. Mitochondrial ROS and TRPM2 channel currents were investigated using flow cytometry and Patch-clamp technique, respectively. TRPM2-/and NLRP3-/mice were used for animal experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
(24 reference statements)
1
15
0
Order By: Relevance
“…IL-1β and IL-18 were confirmed to be products of NLRP3 inflammasome activation [19]. Furthermore, current studies have demonstrated that NLRP3 inflammasome activation plays a key role in the pathogenesis of VILI in a mouse model [17,18]. Therefore, lung-protective ventilation may inhibit inflammatory responses by inhibiting activation of the NLRP3 inflammasome during OLV.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…IL-1β and IL-18 were confirmed to be products of NLRP3 inflammasome activation [19]. Furthermore, current studies have demonstrated that NLRP3 inflammasome activation plays a key role in the pathogenesis of VILI in a mouse model [17,18]. Therefore, lung-protective ventilation may inhibit inflammatory responses by inhibiting activation of the NLRP3 inflammasome during OLV.…”
Section: Discussionmentioning
confidence: 83%
“…Recently, researchers demonstrated that NLRP3 inflammasome activation is important for exacerbating VILI [17,18]. The activation of the NLRP3 inflammasome produces IL-1β and IL-18 [19].…”
Section: Changes In Il-1β and Il-18 In The Balf And Plasmamentioning
confidence: 99%
“…Furthermore, current studies have demonstrated that NLRP3 in ammasome activation plays a key role in the pathogenesis of VILI in a mouse model [25,26]. Therefore, lung protective ventilation may inhibit in ammatory responses by inhibiting the activation of the NLRP3 in ammasome.…”
Section: Discussionmentioning
confidence: 86%
“…This hinders airway which might cause the incident of PPCs as an outcome 24 . Moreover, this type of surgery had long surgical time or mechanical ventilation time (mostly more than 3 hours), which might cause ventilation induced lung injury (VILI) 25 , and had limb ischemia-reperfusion injury due to the use of the tourniquet in the thigh area, which might induce remote lung damage 26 . Except that, after the type of surgery, due to the microvascular reconstruction technique in the neck region, patients are required to stay lying in bed restraining lots of neck movement for at least three days after surgery, which might bring about respiratory muscle complications and mouth ejection and even PPCs 27 .…”
Section: Discussionmentioning
confidence: 99%